Characterization of high‐latitude ionospheric scintillation of GPS signals. Issue 6 (6th December 2013) - Jiao, Yu; Morton, Yu T.; Taylor, Steven; Pelgrum, Wouter
Abstract [1] This paper presents statistical analysis of arctic auroral oval ionospheric scintillation events during the current solar maximum based on high‐rate Global Positioning System data collected in Gakona, Alaska (62.39°N, 145.15°W) from August 2010 to March 2013. The objective is to gain a better understanding of the climatology and morphology of ionospheric scintillation in high‐latitude regions. A scintillation event filter, multipath identification procedures, and other processes are applied to exclude nonscintillation related signal intensity and phase fluctuation and to extract scintillation events with S4 index above 0.12 and phase sigma above 6° from over 657 days of data. A total of over 5800 scintillation events were identified; most of them show phase fluctuations, only 10% of the phase fluctuations are accompanied by weak amplitude scintillation. Based on the occurrence time, signal direction of arrival, intensity, and duration of these scintillation events and the solar and geomagnetic activities associated with these events, diurnal, seasonal, spatial, and solar activity dependencies are derived and presented in the paper.